2015
DOI: 10.1063/1.4905873
|View full text |Cite
|
Sign up to set email alerts
|

Bulk GaN flip-chip violet light-emitting diodes with optimized efficiency for high-power operation

Abstract: We report on violet-emitting III-nitride light-emitting diodes (LEDs) grown on bulk GaN substrates employing a flip-chip architecture. Device performance is optimized for operation at high current density and high temperature, by specific design consideration for the epitaxial layers, extraction efficiency, and electrical injection. The power conversion efficiency reaches a peak value of 84% at 85 °C and remains high at high current density, owing to low current-induced droop and low series resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
126
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(130 citation statements)
references
References 27 publications
3
126
0
1
Order By: Relevance
“…The thermoelectrical pumping effects in LEDs of various wavelength were also observed and reported by experimentalists. [10][11][12][13] The first observation of η W P E > 1 is reported in 2012 when Santhanam et al used lock-in measurement tools to demonstrate an infrared GaInAsSb/GaSb LED with η W P E over 200% at 135 • C. 1 In 2013, higher-than-unity η W P E was achieved in mid-infrared LEDs at room temperature. 14 All these ultra-efficient LEDs operated at extremely low bias (qV kT ), and their output power densities were merely several hundreds nW/cm 2 , which is not enough for direct observation of temperature drop.…”
Section: Previous Work On Ultra-efficient Ledsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermoelectrical pumping effects in LEDs of various wavelength were also observed and reported by experimentalists. [10][11][12][13] The first observation of η W P E > 1 is reported in 2012 when Santhanam et al used lock-in measurement tools to demonstrate an infrared GaInAsSb/GaSb LED with η W P E over 200% at 135 • C. 1 In 2013, higher-than-unity η W P E was achieved in mid-infrared LEDs at room temperature. 14 All these ultra-efficient LEDs operated at extremely low bias (qV kT ), and their output power densities were merely several hundreds nW/cm 2 , which is not enough for direct observation of temperature drop.…”
Section: Previous Work On Ultra-efficient Ledsmentioning
confidence: 99%
“…13 The packing processes are also mature and widely applied in commercial LEDs. However, as we will discuss in 2, due to the large surface area and thermal mass of an encapsulated LED, we need eliminate the package to maximize the ELC temperature drop.…”
Section: Extraction Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a recent report demonstrates WPE exceeding 80% for a gallium-nitride-based LED [1], which inevitably leads to questions about further enhancement towards the conventional limit of unity efficiency. Nevertheless, theory and experiments suggested that for light-producing devices such as LEDs, the WPE may exceed unity in practice [2][3][4][5][6][7][8][9][10][11][12][13] since the incoherent electroluminescent radiation emitted has finite entropy.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] This limits strongly the LED efficiency at current densities above 100 A/cm 2 and therefore prevents LEDs from being used efficiently in applications requiring very high output powers. Very recently, Hurni et al demonstrated how current crowding can be reduced by using a thick n-type current-spreading layer, 6 but this still requires expensive bulk GaN substrates as well as large n-type contacts.…”
Section: Introductionmentioning
confidence: 99%